Docência na educação profissional no IFES e no SENAI-ES : estudo comparativo da inserção, formação e condição de trabalho no curso Técnico em Mecânica - Januário, Tatiana das Mercês (2018)
This research focuses on the Technical Professional Education of the Middle Level (EPTNM), with the main objective of analyzing and comparing the teaching in this field, from the insertion, the training, the working conditions and the practice of the teachers of the Technical course in Mechanics in Senai-ES and Ifes. It was based on the theoretical-methodological contribution of historical and dialectical materialism, and dialogues mainly with Frigotto (2010), Kuenzer (2010), Moura (2008) and Machado (2008). From a predominantly qualitative approach, using the comparative analysis method, the research described, analyzed and compared two specific realities of the EPTNM, having as research instruments: the documentary analysis, the on-site visit and the speeches of the registered subjects through semi-structured interviews. The similarities between these institutions are revealed through: tradition, reference and social prestige in the provision of EFAIDS courses; the infrastructure of classrooms, workshops and laboratories; curriculum (course plan); and student profile. The differences between these institutions are revealed through: the legal nature; administrative and pedagogical organizations; of its aims, objectives and missions; of their conceptions of professional education; of teaching work (contract, salary and career plan); of the teacher-institution-student relationship; profile of teachers; and teaching practice. These characteristics define the identity of each of the institutions studied and have implications for teaching, defining their limits of performance and training. Thus, this research favors the understanding that the insertion, training and working conditions of the teacher can determine their teaching practices. It also highlights the importance of teacher training in the EPTNM as a space that can help the teacher to understand the world of work and create educational actions that allow the formation of workers aware of their reality and able to face the conditions imposed by capital.